Egg-yolk core–shell mesoporous silica nanoparticles for high doxorubicin loading and delivery to prostate cancer cells. Issue 18 (20th April 2022) - Tiburcius, Steffi; Krishnan, Kannan; Jose, Linta; Patel, Vaishwik; Ghosh, Arnab; Sathish, C. I.; Weidenhofer, Judith; Yang, Jae-Hun; Verrills, Nicole M.; Karakoti, Ajay; Vinu, Ajayan
Abstract : A simple synthesis strategy for constructing yolk–shell mesoporous silica nanoparticles is reported for enhanced drug delivery of chemotherapeutic drugs. Abstract : Mesoporous silica-based nanoparticles (MSNs) have gained rapid interest as a drug delivery system (DDS) and demonstrated their versatility in delivering drugs for the treatment of various cancers. However, the drug loading efficiency of MSNs is low and is usually improved by improving textural properties through complicated synthesis methods or by post synthesis modification of the surface that can result in the loss of surface area and modify its drug release properties. In this study, we report a direct single-step synthesis of MSNs with a unique egg-yolk core–shell morphology, large pore volume and a hydrophilic surface, decorated with nitrogen rich surface functionalities for increasing its drug loading capacity. This combination of excellent textural properties and surface functionalisation was achieved by a simple soft templating method using dual surfactants and the silica sources assisted by employing either triethylamine (TEA) or triethanolamine (TEO) as the hydrolysis agent. The morphology and well-ordered mesoporous structure can simply be tuned by changing the pH of the synthesis medium that affects the self-assembly mechanism of the micelles. HRTEM image of samples clearly revealed an egg-yolk core–shell morphology with a thin mesoporous silica shell. The optimised MSN samples synthesized at a pH of 11 using either TEA or TEO depicted a higher doxorubicin (Dox) loading capacity of 425 μg mg −1 and 481 μg mg −1 respectively, as compared to only 347 μg mg −1 for MSN samples due to the uniform distribution of nitrogen functionalities. The anticancer activity of Dox loaded MSNs evaluated in two different prostate cancer cell lines (PC-3 and LNCaP) showed a higher cytotoxicity of the drug loaded on optimised MSN samples as compared to pristine MSNs without affecting the cellular uptake of the particles. These results suggest that the unique single-step synthesis and functionalisation method resulted in successfully achieving higher drug loading in egg-yolk core–shell nitrogen functionalised MSNs and could be implemented as an effective carrier of chemotherapeutic drugs.